The Phytase and Microbial Potential in Fish Feed: A Review - Haetami, Kiki; Amanda, Trisna Rosa; Abun, Abun (Jurnal Biologi Tropis, 2025)
Phytic acid is a form of phosphorus storage that can interfere with the absorption of starch and protein as an energy source from cereal grain flour. This review aims to explore the benefits of microbial fermentation processing in producing phytase enzymes to degrade phytic acid and improve the nutritional quality of grain-based fish feed. Through a comprehensive literature study approach, reviewing the mechanism of phytase production, characteristics of potential microbes, and fermentation process optimization strategies that can affect the effectiveness of enzymes in reducing phytic acid content. The results of the study showed that the microbes Bacillus subtilis, Aspergillus niger, and Lactobacillus plantarum have the potential to produce phytase. Optimization of environmental conditions in fermentation and phytase application is influenced by media composition, environmental parameters, microbial strains and fish species, becoming the key to the success of effective enzyme application. Optimal fermentation conditions range from pH 4.5-6.5 and temperature 45-55℃. Addition of phytase with a dose of 0.75-2 g/kg feed can increase growth. Phytase can increase digestibility and is effectively needed (range 500-1500 mg/kg) in farmed fish.